Nonclassical Patrolling Monocyte Function in the Vasculature. Issue 6 (June 2015) - Thomas, Graham; Tacke, Robert; Hedrick, Catherine C.; Hanna, Richard N.
Abstract : Nonclassical patrolling monocytes are characterized by their unique ability to actively patrol the vascular endothelium under homeostatic and inflammatory conditions. Patrolling monocyte subsets (CX3CR1 high Ly6C − in mouse and CX3CR1 high CD14 dim CD16 + in humans) are distinct from the classical monocyte subsets (CCR2 high Ly6C + in mouse and CCR2 high CD14 + CD16 − in humans) and exhibit unique functions in the vasculature and inflammatory disease. Patrolling monocytes function in several disease settings to remove damaged cells and debris from the vasculature and have been associated with wound healing and the resolution of inflammation in damaged tissues. This review highlights the unique functions of these patrolling monocytes in the vasculature and during inflammation.